Developing and validating an integrated instrument for nursing assessments in adult hospitalization units: Study protocol - David Luna‐Aleixos; Víctor M. González‐Chordá; Marta Aquilué‐Ballarí; Irene Llagostera‐Reverter; Gema Mecho‐Montoliu; Águeda Cervera‐Gasch; María Jesús Valero‐Chillerón; Desirée Mena‐Tudela; Laura Andreu‐Pejó (Wiley, 2023)
Abstract Aims To develop and validate an instrument that integrates functional capacity, risk of pressure ulcers and risk of falling with a more parsimonious approach towards nursing assessments in hospitalization units. Design Cross‐sectional validation multicentre study. Methods Socio‐demographic variables and assessments of Barthel Index, Braden Index and Downton Scale are included via electronic health records. Instrument's development process will include: (i) conceptual assessments; (ii) content validity; (iii) construct validity; (iv) internal consistency and (v) interobserver reliability. The analysis will consider possible differences in medical and surgical hospitalization units, hospitalization type or being a COVID‐19 patient. This study was accepted for funding in November 2020 and approved by the Ethics and Research Committee in January 2021. Results An integrated instrument that lowers the administrative load of nursing assessments and allows at‐risk patients to be detected with at least the same validity and reliability as the original instruments is expected to be obtained.